فعالية استخدام وسيلة اللعبة "الحقيقة أو الجرأة" لترقية مهارة الكلام لدى الطلاب بالمدرسة: The Effectiveness of Using the “Truth or Dare” Game as a Learning Tool to Improve Students’ Speaking Skills at School - Nabila Izzatul Ufairah; Habib Luthfi; Slamet Daroini; Nadia Arrifqi; Pahrurrozi Pahrurrozi; Nurlina Siregar (Journal of Arabic Language Teaching, 2026)
Arabic language learning requires effective instructional media to develop students’ communicative competence, particularly in speaking skills. However, existing studies on the use of game-based media, especially the Truth or Dare game, remain limited in addressing the systematic development of Arabic speaking skills at the secondary school level. This study aims to examine the effectiveness of the Truth or Dare game in improving students’ Arabic speaking skills at State Islamic Senior High School 2 Jember. A quantitative approach with a quasi-experimental design using unequal control groups was employed, involving an experimental and a control class. Data were collected through observation, interviews, pre-tests, and post-tests, and analyzed using SPSS 27 through normality and independent sample t-tests. The results showed that the data were normally distributed (Sig. > 0.05) and revealed a statistically significant difference between the two groups (t = -4.773; Sig. 0.000 < 0.05), indicating that the Truth or Dare game significantly improves students’ speaking skills. This study highlights the innovative role of interactive game-based learning in enhancing students’ confidence, creativity, and fluency. The findings contribute both theoretically and practically by supporting the integration of interactive media in Arabic language teaching. It is recommended that teachers adopt such media to promote active learning. يتطلب تعلم اللغة العربية وسائل تعليمية فعالة لتنمية الكفاءة التواصلية لدى الطلاب، لا سيما في مهارات التحدث. ومع ذلك، لا تزال الدراسات الحالية حول استخدام الوسائل القائمة على الألعاب، وخاصة لعبة «الحقيقة أو الجرأة»، محدودة في معالجة التطوير المنهجي لمهارات التحدث باللغة العربية على مستوى المرحلة الثانوية. تهدف هذه الدراسة إلى فحص فعالية لعبة «الحقيقة أم التحدي» في تحسين مهارات التحدث باللغة العربية لدى الطلاب في المدرسة الثانوية الإسلامية الحكومية رقم 2 بجمبر. تم استخدام نهج كمي بتصميم شبه تجريبي باستخدام مجموعات مراقبة غير متساوية، شملت فصلاً تجريبياً وفصلاً مراقبة. تم جمع البيانات من خلال الملاحظة والمقابلات والاختبارات التمهيدية والاختبارات النهائية، وتم تحليلها باستخدام برنامج SPSS 27 من خلال اختبارات التوزيع الطبيعي واختبارات t للعينات المستقلة. أظهرت النتائج أن البيانات موزعة توزيعًا طبيعيًا (Sig. > 0.05) وكشفت عن وجود فرق ذي دلالة إحصائية بين المجموعتين (t = -4.773؛ Sig. 0.000 < 0.05)، مما يشير إلى أن لعبة "الحقيقة أم التحدي" تحسن مهارات التحدث لدى الطلاب بشكل ملحوظ. تسلط هذه الدراسة الضوء على الدور المبتكر للتعلم التفاعلي القائم على الألعاب في تعزيز ثقة الطلاب وإبداعهم وطلاقتهم. وتسهم النتائج نظريًا وعمليًا في دعم دمج الوسائط التفاعلية في تدريس اللغة العربية. ويوصى بأن يتبنى المعلمون هذه الوسائط لتعزيز التعلم النشط.